POTENSI PESTISIDA EKSTRAK BATANG BROTOWALI (Tinospora crispa. L) SEBAGAI PENGENDALIAN LARVA KUMBANG TANDUK (Oryctes rhinoceros L.) - Muliani, Muliani; Amperawati, Suharyani; Octoviani, Ninie Dwi (Universitas Gunadarma, 2024)
Brotowali stems (Tinaspora crispa. L) contains compounds that can be used as vegetable pesticides. The purpose of this study was to determine the phytochemical content present in brotowali stems, and effective concentrations of brotowali on mortality of O. rhinoceros larvae. This study used a Factorial Complete Ran domized Design with 6 treatments and 3 repeats, using concentrations of 0%, 10%, 10%, 20%, 30%, 40%, and 50%. The first factor is brotowali stem extract and the second factor is the method of application. The parameters observed were yield, phytochemical compounds, mortality, time of death 50% (LT50), and Lethal concentration (LC50). The results showed that brotowali stem extract contains phytochemical compounds, namely alkaloids, flavonoids, tannins, saponins, steroids, and terpenoids. The yield produced from the rotary evaporator is 12.6%. Giving brotowali stem extract had a very real effect on the mortality of O. rhinoceros. BNJ further tests showed that 50% treatment had a very real effect with mortality of 66.67% in the feed application method, on the 11th day with a concentration of 50% and 40% feed method, then for an effective concentration to kill O. rhinoceros larvae, 50% was a concentration of 37.23% in the feed application method while in the spray application method, it could kill O. rhinoceros larvae 50% with a concentration of 63.86%.